2017
DOI: 10.1515/euco-2017-0001
|View full text |Cite
|
Sign up to set email alerts
|

A minimum indicator set for assessing fontanili (lowland springs) of the Lombardy Region in Italy

Abstract: This paper reports on the issue of fontanili assessment. A fontanile is a lowland spring, excavated by humans for the use of underground water for irrigation. From the XII century on, fontanili have been dug to extend water availability throughout the year and increase agricultural land use in the lowlands of Northern Italy. Because water of the fontanile stays at temperature without great changes throughout the year (between 8 and 15°C), this environment is host to a vast variety of flora and fauna and has ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…To regularly monitor the chemical-physical water parameters of springwells would be advisable, as well as of the aquifers in densely populated and industrialized areas (De Caro et al 2017) to highlight possible critical circumstances where to act for the conservation/restoration of these environments. Monitoring data of water and other ecological parameters could be useful to develop innovative instruments (or implement already existing ones) to help territorial managers to decide which wetlands need primarily an intervention of restoration, as realized by Almendinger (1998) and Fumagalli et al (2017). These instruments would be even more effective if supported by data collected in the field.…”
Section: Parametermentioning
confidence: 99%
See 2 more Smart Citations
“…To regularly monitor the chemical-physical water parameters of springwells would be advisable, as well as of the aquifers in densely populated and industrialized areas (De Caro et al 2017) to highlight possible critical circumstances where to act for the conservation/restoration of these environments. Monitoring data of water and other ecological parameters could be useful to develop innovative instruments (or implement already existing ones) to help territorial managers to decide which wetlands need primarily an intervention of restoration, as realized by Almendinger (1998) and Fumagalli et al (2017). These instruments would be even more effective if supported by data collected in the field.…”
Section: Parametermentioning
confidence: 99%
“…Among GDEs, spring-wells are unique ecosystems dependent on the groundwater outflow (EC 2015). The spring-wells provide water with relatively constant temperature (8-15 °C) (Fumagalli et al 2017): seasonal variations affect the water temperature with a delay of 2-4 months, making the coldest period in April and the warmest in October, creating particular environments where rare plants and animals of community interest can live (Bertolani Marchetti 1959;Pisoni and Valle 1992;Viaroli et al 2003;De Luca et al 2005;Frattini 2008;Alessandrini et al 2011;Bischetti et al 2012). For this reason, the spring-wells are included in the Habitat Directive of the European Union (EC 1992) but most of them are currently at risk due to degradation processes happened mainly in the Sixties (Bischetti et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These categories consider parameters and indicators which require analyzes of areas larger than the interface area, defined as the area consisting of the 50-meter width continuous to the PPA (Permanent Preservation Areas, according to Brazilian law), as specified by Rosso Pinto 2019. Thus, the area of 1-kilometer buffer around the spring was applied for this stage using GIS, as established by the protocol, which was based on Fumagalli et al (2017). For this phase, it was necessary to obtain and process spatial data, such as water network, identification of the springs, and the 1-kilometer buffer for mapping the land use and occupation classes.…”
Section: Protocol For Integrated Assessment and Monitoring Of Springs...mentioning
confidence: 99%
“…In the Oglio River, the groundwater heads in the shallow aquifer of the higher plain are lowest in spring, at the end of the non-irrigation period, and increase by about 4 m during the irrigation period [40]. Numerous springs located in the spring belt area have null discharge for most of the year, with the irrigation period being the exception [58,80,81]. Recent studies have demonstrated that the main source of recharge (>50%) to the Oglio River higher plain aquifer is irrigation water [40].…”
Section: Irrigation As An Important Component Of the Hydrological Cycmentioning
confidence: 99%